(untitled) (Medical Forum Monthly, 2021)
Objective: The objective of this study to evaluate the effect of honey for control of infection in patients with Sore throat. Study Design: Case-control study Place and Duration of Study: This study was conducted at the department of ENT of Federal Post-Graduate Institute Shaikh Zayed Hospital, Lahore and Department of Physiology of Islam Medical College, Sialkot from March 2019 to July 2020 for a period of 15 months. Materials and Methods: Patients were randomly assigned to one of two groups: study or control. We had 200 patients in the research group. Left over 200 patients in the control group were put only on antibiotics, anti-inflammatory drugs and gargles without honey. The patients were assessed after 5 days, 10 days, and 15 days after starting the treatment. Results: Both Male and female patients were equal in this study. Honey-using trial participants recovered from sore throats faster than the control group. In terms of individual signs and symptoms, the study group recovered from fever substantially faster than the control group within 5 days. In the study group, indications of oropharyngeal congestion also recovered faster. In both groups, there was no significant difference in the number of patients who were lost to follow-up. Conclusion: Honey prompts quicker recuperation of signs and manifestations of sore throat. Thus, we can infer that admission of honey adjuvant treatment would help patients with sore throat.